Cross-border mergers & acquisitions and the role of trade costs - Hijzen, Alexander. (European Economy. Economic papers, 2006)
Cross-border mergers and acquisitions (M&As) have increased dramatically over the last two decades. This paper analyses the role of trade costs in explaining the increase in both the number and the value of cross-border mergers and acquisitions. In particular, we distinguish horizontal and non-horizontal M&As and investigate whether distance and trade policy barriers affect these two types of mergers differently. We analyse this question using industry data for 23 OECD countries for the period 1990-2001. Our findings suggest that while in the aggregate trade costs affect cross-border merger activity negatively its impact differs importantly across horizontal and non-horizontal mergers. The impact of trade costs is less negative for horizontal mergers, which is consistent with the tariff-jumping argument.